REVIEW OF MAQASHID SHARIA IN THE EXISTENCE OF PRISAI SAKTI MATARAM DURING THE COVID-19 PANDEMIC - Prameswara Samofa Nadya; Muhammad Ariq Ramadhan; Hidajat Sofjan Widjaja (Proceeding International Seminar of Islamic Studies, 2023)
Prisai Sakti Mataram is one of the Indonesian Pencak Silat Organization affected by the Covid-19 pandemic. This research was conducted to explore aspects of religiosity and creativity in improving the existence of organization during the pandemic and then analyse them in the maqashid sharia aspect. The research is conducted to be qualitative method by interviewed the active members of Prisai Sakti Mataram DKI Jakarta which is selected by the criteria set by the authors. The result is all the aspects that are built to improve the existence of organization have met and are in line with the elements in maqashid sharia. This includes the empowerment of creativity and religiosity aspects carried out by the members of Prisai Sakti Mataram who have fulfilled the maqashid sharia elements related to efforts to improve the existence of their colleges during the Covid-19 pandemic.